Iman Membimbing, Musyawarah Menyatukan - Cilsyla Ayu Oktaviani; Yulia Y; Indana Zulfa; Clara Siti Sadiah; Refa Putri Fauzia, Yusuf firmansyah; Fahd Ilham, Ilham irfandi; Daud Hasan, Fitrahudin; Dian Herdiana, Rahmat Solihin (Yayasan Daarul Huda Kruengmane, 2025)
The application of Pancasila values, particularly the First Principle of “Belief in One God” and the Fourth Principle of “Democracy guided by the wisdom of deliberation among representatives,” is important to be implemented from an early age so that students have behavior based on faith and are able to deliberate wisely. This actualization activity was carried out by the Pancasila Education Course Group at UIN Sunan Gunung Djati Bandung at MTs Ar-Rosyidiah, Pasir Batu, on October 30, 2005. The purpose of this activity was to provide an understanding of the importance of faith, manners as part of divine character, and the ethics of deliberation. The activity was carried out using the Classroom Action Research (CAR) method through the stages of planning, action, observation, and reflection. The results of the activity showed an increase in students' ability to express their opinions politely, respect their friends' opinions, and understand that deliberation must be based on faith. Games, light discussions, and rewards helped increase student participation and awareness of manners. This activity proves that connecting the values of faith and deliberation can strengthen positive habits in learning and interacting.